PENGEMBANGAN KAPITAL SOSIAL KOMUNITAS DESA (Studi Kasus Pada Komunitas Desa Siaga Nagarawangi Di Kecamatan Rancakalong Kabupaten Sumedang) - Sri Sulastri (Indonesian Journal of Dialectics, 2012)
Community social capital is often used to explain of health inequalities. Therefore, the development of community social capital undertaken to address the health inequality. Through the Program of Pengembangan Desa Siaga, the Desa Siaga Nagarawangi Community considered successfully improved community social capital. This paper is intended to explain the process of improving social capital at the Desa Siaga Nagarawangi and the usefulness for prevention and treatment of health problems. This research method is a case study, which uses a single case (embedded) design, the design of case studies to study the single case that has more than one unit of analysis. As a reference in the process of collecting and analyzing data used Community Social Capital Construction Theory that was developed Warner (1999) and the theory of Community Social Capital developed Uphoff (2000). From this study can be formulated conceptualization determinants of social network expansion and determinants of the sustainable of sociality in the network that can be used to make the construction of Community Social Capital Improvement Model.